2021
DOI: 10.1088/1755-1315/748/1/012035
|View full text |Cite
|
Sign up to set email alerts
|

Managerial Aspect and Digital Marketing of Micro, Small and Medium Enterprises in West Java

Abstract: Changes in economic order in the new normal era have an impact on the marketing and managerial aspects of Micro, Small and Medium Enterprises (MSMEs). Many MSMEs have not yet used digital marketing so that they experienced a significant decline in sales and have not been able to overcome managerial problems. This research method is designed as a survey research with a descriptive approach using narrative analysis tools. The population in this study are MSMEs in West Java selected through cluster random samplin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
1
0
3
Order By: Relevance
“…This research was conducted from June to November 2021, and the questionnaire distributed in October, with focus of the study scope in West Java province. West Java province has the potential for business development through the increasing number of MSMEs sector every year in each city and regency, for example in 2020 the number of MSMEs in West Java province reaches two million which indicate the great potential for community economic development (Hernita & Ginanjar, 2021;Primatami & Hidayati, 2019). Previous study has shown that the MSMEs practitioners in West Java has high category of work ethic which is relevant to deal with the challenge of ASEAN economic community (Harding, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…This research was conducted from June to November 2021, and the questionnaire distributed in October, with focus of the study scope in West Java province. West Java province has the potential for business development through the increasing number of MSMEs sector every year in each city and regency, for example in 2020 the number of MSMEs in West Java province reaches two million which indicate the great potential for community economic development (Hernita & Ginanjar, 2021;Primatami & Hidayati, 2019). Previous study has shown that the MSMEs practitioners in West Java has high category of work ethic which is relevant to deal with the challenge of ASEAN economic community (Harding, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Jawa Barat dikenal sebagai provinsi penghasil Usaha Mikro, Kecil, dan Menengah (UMKM) terbesar di Indonesia, dengan sektor pangan menjadi salah satu sektor yang paling banyak digarap Hernita & Ginanjar, 2021). Namun, pandemi Covid-19 berdampak pada penurunan pendapatan UMKM di Jawa Barat, dan sebagian UMKM di bidang pangan masih belum mampu menyelesaikan masalah manajerial, meskipun produknya belum dipasarkan melalui media online (Nurani et al, 2020).…”
Section: Pendahuluanunclassified
“…Namun, pandemi Covid-19 berdampak pada penurunan pendapatan UMKM di Jawa Barat, dan sebagian UMKM di bidang pangan masih belum mampu menyelesaikan masalah manajerial, meskipun produknya belum dipasarkan melalui media online (Nurani et al, 2020). Untuk mendukung pengembangan UMKM di Jawa Barat, diperlukan kebijakan dan inisiatif yang menjawab tantangan yang dihadapi UMKM, seperti peningkatan akses ke sumber daya dan pemberian program pelatihan dan dukungan (Hernita & Ginanjar, 2021).…”
Section: Pendahuluanunclassified
“…Sebuah studi menemukan bahwa kapabilitas pemasaran digital memiliki pengaruh positif terhadap kinerja UMKM (Odoom et al, 2017;Purwanti et al, 2022;Wardaya et al, 2019). Studi lain menemukan bahwa pemasaran digital dapat mengimbangi aspek pemasaran manual dan meningkatkan keberlanjutan bisnis UMKM (Hernita & Ginanjar, 2021). Selain itu, dicatat bahwa UMKM perlu mengembangkan kemampuan pemasaran mereka dan meningkatkan kinerja pemasaran mereka, yang dapat dicapai melalui pemasaran digital (Hermina et al, 2020).…”
Section: Pendahuluanunclassified